Review the Various Threats specific in Application Layer for speedup to Web Security Evaluation (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The motive of the present study is to pay some light on the contribution of Security in the field of Web. The Web application has become an incredible field in the world of corporate .The SECURITY is defined as overall quality, authenticity, reliability, scalability, confidentiality and authorisation. This research work is about security principles in web applications. This paper is centralised to reach out the attack and threat on web application and resume the concern security principles or method to overcome. According to evidence, exploitable vulnerabilities present in the source code could enable up to 60% of attacks on enterprise web applications. In this article, we examine the different risks unique to the application layer, as well as the associated compensating controls. Threats unique to each tier of an enterprise web application are addressed, with an emphasis on threat modelling. Security is the necessary, significant and cardinal point in web application. The security is the key concept in the world of web. Web application security is an essential key point of concern because it has become a way to interact with the internet and computing system. The methodology to overcome vulnerability is penetration tools, backtracking. Input validation etc.